COVID‐19 pandemic: The impact on vulnerable children and young people in Australia. (15th September 2020) - Jones, Benjamin; Woolfenden, Susan; Pengilly, Sandra; Breen, Christie; Cohn, Richard; Biviano, Lyn; Johns, Adam; Worth, Andrea; Lamb, Robyn; Lingam, Raghu; Silove, Natalie; Marks, Susan; et al.
Abstract : The COVID‐19 pandemic and associated system disruptions are impacting all children and young people (CYP) in Australia. For vulnerable groups of CYP, who already experience poorer health and well‐being, these impacts are amplified. Challenges include reduced access to usual services, reduced community supports, financial instability, unemployment and other life circumstances that threaten to widen pre‐existing inequities. This article aims to present the reasons for vulnerability of CYP during the pandemic, and to focus on actions by health professionals that mitigate additional challenges to their health and well‐being. Using a rapid review of the literature and team‐based discussions, eight vulnerable groups were identified: CYP with disabilities, mental health conditions and chronic diseases; CYP facing financial hardship; within the child protection system; Aboriginal; migrant and refugee; in residential care; rural; and isolated CYP. Recommendations for action are required at the level of governments, health professionals and researchers and include enhancing access to health and social supports, prioritising vulnerable CYP in resuming health activity and elevating the voice of CYP in designing the response. The pandemic can be conceptualised as an opportunity to create a more equitable society as we document the inequities that have been exacerbated. Vulnerable groups of CYP must be recognised and heard, and targeted actions must focus on improving their health outcomes during the pandemic and beyond.